Assessing Bacillus subtilis biosurfactant effects on the biodegradation of petroleum products - Montagnolli, Renato Nallin; Lopes, Paulo Renato Matos; Bidoia, Ederio Dino (Environmental monitoring and assessment, 2015)
Microbial pollutant removal capabilities can be determined and exploited to accomplish bioremediation of hydrocarbon-polluted environments. Thus, increasing knowledge on environmental behavior of different petroleum products can lead to better bioremediation strategies. Biodegradation can be enhanced by adding biosurfactants to hydrocarbon-degrading microorganism consortia. This work aimed to improve petroleum products biodegradation by using a biosurfactant produced by Bacillus subtilis. The produced biosurfactant was added to biodegradation assays containing crude oil, diesel, and kerosene. Biodegradation was monitored by a respirometric technique capable of evaluating CO₂production in an aerobic simulated wastewater environment. The biosurfactant yielded optimal surface tension reduction (30.9 mN m⁻¹) and emulsification results (46.90 % with kerosene). Biodegradation successfully occurred and different profiles were observed for each substance. Precise mathematical modeling of biosurfactant effects on petroleum degradation profile was designed, hence allowing long-term kinetics prediction. Assays containing biosurfactant yielded a higher overall CO₂output. Higher emulsification and an enhanced CO₂production dataset on assays containing biosurfactants was observed, especially in crude oil and kerosene.